Granulomatous mastitis in a male breast: A case report and review of literature. Issue 3 (2nd March 2023) - Kawashima, Kei; Yamamoto, Shinya; Narui, Kazutaka; Fujiwara, Yoshie; Adachi, Shoko; Sasamoto, Mahato; Oshi, Masanori; Yamada, Akimitsu; Kumagai, Eita; Otani, Masako; Endo, Itaru
Abstract: Granulomatous mastitis (GM) is a rare disease, particularly among men. Herein, we present a case of GM diagnosed in a 63‐year‐old male patient who showed reduction in the tumor size during 3 months of observation. Abstract : The optimal treatment strategy for granulomatous mastitis in men is still controversial due to its rarity. However, observation may be a viable option in asymptomatic cases.